'Breakdown and healing' - adaptation experiences of postpartum nurses returning to work: a descriptive phenomenological study - Tianji Zhou; Xiangling Dong; Lei Zhang; Wenjun Chen; Xing Zhang; Jingping Zhang; Jia Chen (BMC, 2024)
Abstract Background Promoting the work adaptation of nurses returning to work after childbirth is key to improving their physical and mental health and ensuring the quality of nursing care. Although postpartum nurses have reported high work stress and poor adaptation after returning to work, little is known regarding the experiences, problems and further needs. This study aimed to explore the adaptation experiences of postpartum nurses returning to work. Methods This was a qualitative study with descriptive phenomenological approach. Individual semi-structured interviews were conducted between March and May 2023 in four tertiary hospitals in Changsha, mainland China, which were selected using convenience sampling. A total of 16 postpartum nurses returning to work within one year were recruited using purposive sampling and maximum variation sampling. The interviews were analysed using the Colaizzi's 7-step method. Results 'Breakdown and healing' is a strong thread in postpartum nurses' work adaptation. It links 13 subthemes in the interview data, which can be grouped under three overarching themes: (a) changes and challenges of multiple roles; (b) self-coping and social support; and (c) further needs after returning to work. The phrase 'breakdown and healing' reflects the mutual relationship between stress and coping among postpartum nurses. The changes and challenges associated with being required to fulfil multiple roles of mothers, wives and nurses make the subjects feel on the verge of 'breakdown'. When returning to work, most of them move slowly towards 'healing' through positive self-management and support from their partners, families, supervisors and colleagues. Moreover, their ongoing demands and unsolved problems - such as their desire for a workplace that is friendly and serves their needs - were generated by the constant process of 'breakdown and healing'. Conclusions Understanding how postpartum nurses returning to work perceive adaptation experiences is essential for nursing managers, who can use the findings to implement targeted measures to shorten postpartum nurses' maladaptation period after returning to work and promote their work adaptation. This study underscores the critical importance of personalized return-to-work training, flexible work arrangements, support from colleagues and managers, well-established maternal facilities and services, and targeted policy efforts in enhancing postpartum nurses' work adaptation.